2015
DOI: 10.1016/j.jenvrad.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and risk assessment of radionuclides released by Fukushima nuclear accident at the northwest Pacific

Abstract: In order to understand the impact of Fukushima Nuclear Accident (FNA) on the marine environment, seawater and a composite squid (Ommastrephe bartrami) sample were collected on the monitoring cruise XT01 during June 16-July 4, 2011. The concentration levels of Cesium-134, Cesium-137, Strontium-90, Silver-110 m, Cobalt-58 and Cobalt-60 were measured both for the seawater and squid samples. The elevated activity levels of Cesium-134 and Cesium-137 were found in the sampling area. Cesium-134 and Silver-110 m, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 23 publications
0
21
0
2
Order By: Relevance
“…(90) In addition to the literature on land-based accidents, there is a robust literature on past marine releases, including submarine sinkings, release in marine environments from U.K. and French reprocessing plants and, more recently, from the marine release at Fukushima. (89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101) The overarching conclusion in this literature is that the long-term impact of marine release on marine biota and human food sources has been much lower than that found in large land-based releases. There remains uncertainty about the very long-term impacts on both aquatic and terrestrial biota from low-level radioactive contamination.…”
Section: Marine Accident Consequencementioning
confidence: 99%
“…(90) In addition to the literature on land-based accidents, there is a robust literature on past marine releases, including submarine sinkings, release in marine environments from U.K. and French reprocessing plants and, more recently, from the marine release at Fukushima. (89)(90)(91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101) The overarching conclusion in this literature is that the long-term impact of marine release on marine biota and human food sources has been much lower than that found in large land-based releases. There remains uncertainty about the very long-term impacts on both aquatic and terrestrial biota from low-level radioactive contamination.…”
Section: Marine Accident Consequencementioning
confidence: 99%
“…The highest concentration of 137 Cs in the seawater monitoring results were input in the assessment as the environment concentration and the parameters of distribution coefficient (Kd), concentration ratio (CR), dose conversion coefficient of radiation, occupancy factors, uncertainty factor were set as the default value in ERICA Tool. The weighing factors of internal low beta, internal beta/gamma and internal alpha were set as 3.1 and 20 (Yu et al, 2015).…”
Section: April 2017) Isotope 137mentioning
confidence: 99%
“…A large amount of research has been conducted to determine the level of artificial radionuclides in biota samples and to assess the relevant radiological impact on both human and marine species. However, most studies have focused on the concentration of radiocesium in fish (Johansen et al, 2015;Wada et al, 2016), and only a few publications have reported on radionuclides in other marine species (Buesseler et al, 2012;Yu et al, 2015). Few data are available for open-ocean locations as compared to coastal areas, especially from 2011.…”
Section: Introductionmentioning
confidence: 99%